Medical Trainees' Experiences With Dying and Death. (May 2021) - Jedlicska, Nana; Srnová, Dagmara; Scheide, Laura; Wijnen-Meijer, Marjo; Gartmeier, Martin; Berberat, Pascal O.
This study investigates medical trainees' experiences with dying and death, by means of semistructured interviews. Nine medical students and nine residents reported a total of 114 experiences. The great majority of these experiences took place during the final year of medical school. The authors identified the latent characteristics, which illustrate an in-depth understanding of the significance of the described experiences. Three main themes emerged: circumstances of death, personal relationship, and one's own role . The age of the dying person, the extent of suffering, time frame and setting, and the patients' behaviors were factors that influence the perceptions of the experiences. The interviewees reported powerful emotional consternation by the patients' deaths with whom they had developed a close relationship. Failure, helplessness, and guilt were negatively associated perceptions of one's own role. This study illustrates the tension between emotional concern and professional detachment. It highlights the continuing existence of a physician image, in which control represents the key issue.